In vitro digestibility of Flint Hill rangeland forages - Umoh, J.E.; Harbers, L.H.; Smith, E.F.; Whitney, J.; Boggs, Don (Kansas State University. Agricultural Experiment Station, 2011)
We used an in vitro digestibility technique to determine the nutritive value of predominately native bluestem forage on burned and nonburned Flint Hills pastures. We also collected forage samples via esophageal fistulas to get what the animals consumed while grazing selectively. Summary Dry matter (DM) digestibilities for 11 months by both techniques followed changes in climatic conditions. The lowest DM digestibility averaged about 65% in October, 1975, and June, 1976; the highest (about 80%) was between February and March 1976. The grass selected by animals was usually more digestible than that harvested by hand. However, in vitro digestibility of the extrusa may be higher than actual digestibility in the animals when both solid and liquid fractions of the extrusa are collected.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; In vito; Digestibility